KARAKTERISTIK FISIKOKIMIA RICE PAPER DENGAN SUBSTITUSI TEPUNG PEKTIN ALBEDO SEMANGKA (Citrullus lanatus) - Ratih Tiara Dewi; Fitria Syehrin Nabila; Rafida Cahyaningrum; Nur Aini (Faculty of Agricultural Technology, University of Jember, 2022)
Edible rice paper is used for making fresh summer rolls (salad rolls) or fried spring rolls in Vietnamese cuisine, where the rice paper is called bánh tráng or bánh đa nem. Ingredients of the food rice paper include white rice flour, tapioca flour, salt, and water. However, in this study, watermelon albedo pectin flour was added to the formulation. The purpose of this study was to determine the concentration of pectin flour and the effect of watermelon albedo pectin addition on the physicochemical characteristics of rice paper. The addition of pectin flour can produce a product that is elastic, not easily torn, and translucent. The research method used a completely randomized design (CRD) with the research factor being the concentration of watermelon albedo pectin flour which consisted of 6 experimental levels and 4 replications. The concentrations of pectin used were 0.25%, 0.5%, 0.75%, 1%, 1.25%, and 1.5%. Data were analyzed using ANOVA (analysis of variance) and continued with duncan multiple range test (DMRT) at the level of 5%. The variables tested were water content, water activity and rehydration power. Based on the results of this study the addition of watermelon albedo pectin flour on rice paper as much as 1.25% was the best treatment, this was because the water content produced about 11.38% and the rehydration power about 233.27%. There was an increase in water content and water activity, but a decrease in rehydration power, however, the water content test showed that the pectin concentration had no significant effect on the physicochemical characteristics of rice paper. So that the concentration of watermelon albedo pectin only affects the water activity and rehydration power of rice paper. Keywords: pectin, rice paper, watermelon albedo